Cultura emprendedora y capacidad de innovación en los estudiantes de Administración de Empresas de la ESPAM MFL - Basurto Gómez, Miguel Ángel (2024)
The primary objective of the research was to analyze the cultural and educational factors that influence entrepreneurial culture and innovation capacity among Business Administration students at ESPAM MFL. The study was divided into three phases: in the first phase, factors were identified through a literature review, application of techniques, and data collection tools; in the second phase, the variables of entrepreneurial culture and innovation capacity were correlated through statistical analysis using descriptive and inferential analysis techniques to understand their relationship and establish possible causes and consequences of their correlation; finally, in the third phase, an action plan was proposed using the Ishikawa diagram, the prioritization matrix, and the 5W+1H matrix for detailed analysis and action plan development. The results showed that there is a correlation between the studied variables, although not very strong. It was concluded that there is a positive but low influence between the variables, as well as in their indicators concerning required competencies, identification of opportunities, and associativity and collaboration, highlighting a positive focus on female entrepreneurship.